THE BOUNDS OF GENETIC MANIPULATION IN FRONT OF THE BRAZILIAN BIOSAFETY LAW - Atiê Paiva, Giovanna; Villela Florêncio, Stella (Revista Gênero e Interdisciplinaridade, 2023)
This article verifies the main aspects of the legal protection of genetic heritage in Brazil, especially since the entry into force of Law 11.105 / 2005, starting from the importance of setting limits to biomedical experiences, especially those related to genetic engineering techniques, to in order to protect human identity from an irreversible transformation of its own characteristics. The human genome has all the genetic information of the species, but it is the genotype of each individual that differentiates us, forming the individuality of each human being, constituting their genetic heritage. It is about seeking a better definition for the human genetic heritage, considered a right of the personality, both in its individual and collective aspect. The imposition of limits on genetic engineering techniques should not necessarily be done by limiting the freedom of scientific research. Only through adequate legal protection will it be possible to guarantee the correct flexibility that harmonizes, simultaneously, the greatest possible freedom of investigation and the respect for the dignity of the human person, avoiding the occurrence of socially rejectable consequences capable of harming this last value in a way harmful and irreversible.